Effect of time and temperature on the simultaneous formation of heterocyclic amines and polycyclic aromatic hydrocarbons using amino acid and sugar model systems - Ishak, Ainaatul Asmaa' (2021)
The aminoimidazoazaarenes types of heterocyclic amines (AIA-types of HCAs) and the 4PAH of polycyclic aromatic hydrocarbons (PAHs) are chemical compounds that form abundantly in muscle meat cooked at 150°C and above from the reaction between the amino acids and the reducing sugar. Studies on HCAs and PAHs formation are essential as both compounds have been classified as carcinogenic by the International Agency for Research on Cancer (IARC). Many studies on HCAs and PAHs focused on their formation in food samples. However, the most susceptible amino acid and sugar precursor was unable to be identified due to the complex system containing many food components. Chemical model system have the advantages of allowing researchers to study the effect of single precursor on HCAs or PAHs formation as the system contains only the precursor. From using chemical model system, previous studies have identified phenylalanine, proline, and glycine as the amino acids responsible for the formation of the AIA-types of HCAs and the 4PAH that are abundant in cooked muscle meat. Nevertheless, studies on the simultaneous formation are limited although they originated from the same precursor and most reported studies focused on HCAs and PAHs formation separately. There is also limited data on the rate formation involving kinetic studies that can be used to signify the difference between each precursor on the formation of HCAs and PAHs. Therefore, the objective of this study is to identify the most susceptible amino acid (phenylalanine, proline, and glycine) and sugar (glucose, fructose, and sucrose) precursor for the simultaneous formation of HCAs and PAHs at household cooking time and temperature using chemical model system with the adaption of kinetic study. Essentially, this study uses an amino acid model system and a sugar model system to investigate the effects of these precursors on the simultaneous formation of HCAs and PAHs. The used of phenylalanine, proline, and glycine were selected as it was identified by previous studies to from most of the HCAs and PAHs compound. Each amino acid model systems were heated at a household cooking temperature and time ranged from 150°C to 270°C at 4 to 16 minutes. The data obtained were fitted into the first-order model equation, Arrhenius equation, and Eyring equation to determine the rate formation of HCAs and PAHs from different amino acid model systems. In sugar model system, glucose, fructose, and sucrose were chosen since they are commonly found in meat. The formation of HCAs and PAHs were identified and quantified using high performance liquid chromatography (HPLC) equipped with photo diode array (PDA) and fluorescence (FLD) detectors. Gas chromatography – mass spectrometry (GC-MS) screening on the model system containing the most susceptible amino acid and sugar was conducted to identify the possible intermediate compounds causing the formation of HCAs and PAHs and predicting the pathway formation. The findings of this study revealed that heating temperature has higher significant effect over heating time. The presence of various amino acids significantly influenced the types of HCAs and PAHs formed, whereas the presence of sugar highly influenced the amount formed. Furthermore, not all amino acid were able to form HCAs but can easily form PAHs. Phenylalanine was identified as the precursor for imidazoquinoline, imidazoquinoxaline, imidazopyridine; proline was the precursor imidazoquinoxaline, and imidazopyridine; whereas as glycine was the precursor for imidazoquinoline, and imidazoquinoxaline. Interestingly, all three amino acids were the precursor for PAHs which comprises of cata-condensed PAHs (benz[a]anthracene, BaA and chrysene, Chry) and peri-condensed PAHs (benzo[b]fluoranthen, BbF and benzo[a]pyrene, BaP). The results from the kinetic studies revealed that regardless on the types of amino acids used, the simultaneous formation of HCAs and PAHs followed the first-order model and that the reaction was an endothermic and bimolecular reaction. Based on the reaction rate (k) and activation energy (Ea) values obtained from the first-order model and the Arrhenius equation, the formations of HCAs and PAHs in each amino acid (phenylalanine, proline, and glycine) model systems were formed at a relatively different rate. All HCAs and PAHs compounds were identified in the heated system of phenylalanine. Hence, phenylalanine was identified as the most susceptible amino acid for the simultaneous formation HCAs and PAHs followed by glycine and proline. In the sugar model systems, glucose was identified as the most susceptible sugar precursor, forming high amount of HCAs and PAHs. This was then followed by fructose and sucrose. In general, the increased in the amino acid and sugar concentrations resulted in a significant increase in the simultaneous formation of HCAs and PAHs. The GCMS screening on model system with most susceptible amino acid (phenylalanine) and sugar (glucose) precursor identified five compound namely 4-methyl quinoline, methyl-3-phenylpropanoate, 3,6-dibenzylpiperazine-2,5- dione, 3-benzyl-6-methylpiperazine-2,5-dione, and creatinine that were involved in the pathway formation of HCAs and PAHs. It can be concluded that different amino acids highly influence the types of HCAs and PAHs whereas, the reducing sugar highly influence the amount of HCAs and PAHs formed. Their simultaneously formation occurred at a relatively different rate depending on the type of amino acid presence. However, regardless on the type of amino acids, the simultaneous formation follows the first order model and the reaction was an endothermic and bimolecular reaction. Phenylalanine and glucose were identified as the most susceptible precursor for the simultaneous formation of HCAs and PAHs.